Imaging a President: Rawlings in The Ghanaian Chronicle - Osam, E. K. (Legon Journal of the Humanities (19): 109-134, 2008)
The post-independence political history of Ghana is replete with failed civilian and military governments. At the close of the 1970s and the beginning of the 1980s, a young Air Force Officer, Flt. Lt. Jerry John Rawlings, burst onto the political scene through a coup. After a return to civilian rule in 1992, with him as Head of State, he was to finally step down in 2000. For a greater part of his rule, press freedom was curtailed. But with the advent of civilian rule backed by a Constitution that guarantees press freedom, the country experienced a phenomenal increase in privately-owned media. One of these is The Ghanaian Chronicle, the most popular private newspaper in the last years of Rawlings’ time in office. This study, under the influence of Critical Discourse Analysis, examines “Letters to the Editor” published in The Ghanaian Chronicle that focused on Rawlings. Through manipulating various discourse structures, writers of these letters project an anti-Rwalings ideology as a means of resisting what they see as political dominance reflected in Rawlings rule.
Keywords: Rawlings; Critical Discourse Analysis; ideology; Discourse structures